Primary neuroendocrine carcinoma of the breast: A case report of liver and lymph node metastases after eight years from diagnosis. Issue 3 (12th September 2019) - Valente, Irene; Tringali, Giulia; Martella, Eugenia Marta; Pallavera, Lara; D'Aloia, Cecilia
Abstract: Primary neuroendocrine carcinoma of the breast (NECB) is one of the rarest subtypes of breast tumor, and for this reason, there are no data from prospective clinical trials on its optimal management. Its incidence is <0.1% of all breast cancers and <1% of all neuroendocrine tumors. The diagnosis of NECB requires the expression of neuroendocrine markers (chromogranin, synaptophysin, NSE) and the lack of simultaneous neuroendocrine carcinoma in extramammary sites. We present a case of a poorly differentiated neuroendocrine carcinoma (PD‐NEC) metastasized in liver and lymph node after eight years. Mammography, ultrasound imaging, CT, and pathology findings are described.